Decomposition of polynomial matrices into a direct sum of triangular summands - Shavarovskyy, B. Z. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
By using the transformationsSA(x)R(x), whereS andR(x) are invertible matrices, we reduce a polynomial matrixA(x) whose elementary divisors are pairwise relatively prime to a direct sum of irreducible triangular summands with invariant factors on the principal diagonals.